Accuracy of MRI-Based Talar Cartilage Thickness Measurement and Talus Bone and Cartilage Modeling: Comparison with Ground-Truth Laser Scan Measurements. (December 2021) - Lockard, Carly A.; Stake, Ingrid K.; Brady, Alex W.; DeClercq, Madeleine G.; Tanghe, Kira K.; Douglass, Brenton W.; Nott, Erik; Ho, Charles P.; Clanton, Thomas O.
Objective: The purpose of this work was to compare measurements of talar cartilage thickness and cartilage and bone surface geometry from clinically feasible magnetic resonance imaging (MRI) against high-accuracy laser scan models. Measurement of talar bone and cartilage geometry from MRI would provide useful information for evaluating cartilage changes, selecting osteochondral graft sources or creating patient-specific joint models. Design: Three-dimensional (3D) bone and cartilage models of 7 cadaver tali were created using (1) manual segmentation of high-resolution volumetric sequence 3T MR images and (2) laser scans. Talar cartilage thickness was compared between the laser scan– and MRI-based models for the dorsal, medial, and lateral surfaces. The laser scan– and MRI-based cartilage and bone surface models were compared using model-to-model distance. Results: Average cartilage thickness within the dorsal, medial, and lateral surfaces were 0.89 to 1.05 mm measured with laser scanning, and 1.10 to 1.22 mm measured with MRI. MRI-based thickness was 0.16 to 0.32 mm higher on average in each region. The average absolute surface-to-surface differences between laser scan– and MRI-based bone and cartilage models ranged from 0.16 to 0.22 mm for bone (MRI bone models smaller than laser scan models) and 0.35 to 0.38 mm for cartilage (MRI bone models larger than laser scan models). Conclusions: This study demonstrated that cartilage and bone 3D modeling and measurement of average cartilage thickness on the dorsal, medial, and lateral talar surfaces using MRI were feasible and provided similar model geometry and thickness values to ground-truth laser scan–based measurements.